On the Spatiotemporal Nature of Vision, as Revealed by Covered Bridges and Puddles: A Dispatch from Vermont. (November 2021) - Caplovitz, Gideon Paul
Retinal painting, anorthoscopic perception and amodal completion are terms to describe visual phenomena that highlight the spatiotemporal integrative mechanisms that underlie primate vision. Although commonly studied using simplified lab-friendly stimuli presented on a computer screen, this is a report of observations made in a novel real-world context that highlight the rich contributions the mechanisms underlying these phenomena make to naturalistic vision.